Children's appraisals of threat in pediatric cancer - Marcia A. Winter; Jessica Greenlee; Nour Al Ghriwati; Katlyn N. Garr; Olle Jane Z. Sahler; Thomas G. O'Connor (Elsevier, 2021)
Purpose: Although many children with cancer cope well with challenges, some experience distress that results in poor adjustment. Children's perceptions of threat may be one explanation for heterogeneity in outcomes, but relatively little is known about what children find threatening. This study aimed to describe the threats that children report. Method: Youth (4-18 years old) newly diagnosed with cancer and their primary/parent caregivers (PC) participated in a multi-method study. Appraisals of threat were assessed via self-report and a narrative technique at two weeks post-diagnosis. PCs reported children's anxiety and depressive symptoms three months post-diagnosis and children reported their quality of life (QOL) six months post-diagnosis. Results: Youth reported various types of threatening events (e.g., receiving the cancer diagnosis, fear or pain of procedures) across multiple domains (e.g., threat to self, physical threat, threat of loss). Adolescents tended to report threat to life (e.g., the seriousness of the diagnosis itself) whereas younger children reported other threats (e.g., procedural pain). Children with high perceived threat to self had higher subsequent anxiety symptoms and lower QOL compared to those with low appraisals of threat to self. There was also a significant mean difference between high and low appraisals of threat of loss in child reported QOL. Conclusions: Youths' reported threats, as well as how threat appraisals related to adjustment outcomes in distinct ways, underscores the developmental nature of how youth interpret medically stressful events and the utility of developmentally sensitive assessment. Understanding perceived threat could ultimately inform efforts to foster positive long-term adaptation for youth with cancer.